Spatially resolved multimode excitation for smooth supercontinuum generation in a SiN waveguide - Kou, Rai; Ishizawa, Atsushi; Yoshida, Koki; Yamamoto, Noritsugu; Xu, Xuejun; Kikkawa, Yugo; Kawashima, Kota; Aihara, Takuma; Tsuchizawa, Tai; Cong, Guangwei; Hitachi, Kenichi; Nishikawa, Tadashi; et al. (Optics express, 2023)
We propose a method of supercontinuum light generation enhanced by multimode excitation in a precisely dispersion-engineered deuterated SiN (SiN:D) waveguide. Although a regularly designed SiN-based nonlinear optical waveguide exhibits anomalous dispersion with the fundamental and first-order multimode operation, the center-symmetric light pumping at the input edge has so far inhibited the full potential of the nonlinearity of SiN-based materials. On the basis of numerical analysis and simulation for the SiN:D waveguide, we intentionally applied spatial position offsets to excite the fundamental and higher-order modes to realize bandwidth broadening with flatness. Using this method, we achieved an SNR improvement of up to 18 dB at a wavelength of 0.6 µm with an offset of about 1 µm in the Y-axis direction and found that the contribution was related to the presence of dispersive waves due to the excitation of TE 10 , and TE 01 modes.